Photoluminescence tuning of Ca8−xSrxMgGd(PO4)7:Eu2+, yMn2+ phosphors for applications in white LEDs with excellent color rendering index. Issue 31 (31st March 2017) - Long, Jiaqi; Wang, Yuzhen; Ma, Chaoyang; Yuan, Xuanyi; Dong, Wenfeng; Ma, Ran; Wen, Zicheng; Du, Miaomiao; Cao, Yongge
Abstract : Two series of novel phosphors of green-yellow emitting Ca8− x Sr x MgGd(PO4 )7 :Eu 2+ and yellow-orange emitting Sr8 MgGd(PO4 )7 :Eu 2+, y Mn 2+ were successfully synthesized by a solid-state reaction. Abstract : Two series of novel phosphors of green-yellow emitting Ca8− x Sr x MgGd(PO4 )7 :Eu 2+ and yellow-orange emitting Sr8 MgGd(PO4 )7 :Eu 2+, y Mn 2+ were successfully synthesized by a solid-state reaction. The crystal structures, photoluminescence (PL), PL excitation (PLE) spectra and decay times were investigated in detail. Upon excitation at 350 nm, the Ca4 Sr4 MgGd(PO4 )7 :Eu 2+ phosphor showed strong green emission centered at 513 nm, and the Sr8 MgGd(PO4 )7 :Eu 2+ phosphor showed strong yellow emission centered at 513 nm and 593 nm, and Sr8 MgGd(PO4 )7 :Eu 2+, Mn 2+ showed strong orange emission centered at 510 nm and 616 nm. In addition, a standard warm white-light emitting single-phased phosphor of Sr8 MgGd(PO4 )7 :Eu 2+, Mn 2+ with chromaticity coordinates ( x, y ), correlated color temperature (CCT) and Commission Internationale de l'Eclairage (CIE) coordinates of (0.4497, 0.3929), 2705 K, and 89.7 was realized via energy transfer between Eu 2+ and Mn 2+ . The energy transfer was demonstrated to be a resonant type dipole–quadrupole mechanism. Moreover, the obtained LED device exhibits an excellent color-rendering index ( R a = 97) at a correlated color temperature of 5651 K with the CIE coordinates (0.3290, 0.3410).